High-wear-resistance ceramic enhanced polymer composite material and preparation method thereof
By adding surface-modified alumina ceramic filler and carbon fiber to the polymer material, and adopting optimized injection molding process and ion bombardment treatment, the insufficient performance of polymer materials in high-strength wear and high temperature environments is solved, and high resistance is achieved Abrasiveness and stability, suitable for applications such as false twisters of elastic feeders.
Patent Information
- Application Number
- CN202411333992.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-17
AI Technical Summary
Existing polymer materials are prone to stick and wear under high-strength wear environments, and are prone to soften or melt in high-temperature environments, resulting in limited life and poor performance of ceramic fillers in high-temperature environments.
Polypropylene resin is used as the matrix and surface-modified alumina ceramic filler and carbon fiber are added. By optimizing the formula ratio and injection molding process parameters, combined with ion bombardment surface treatment, a high-wear resistance ceramic reinforced polymer composite material is prepared.
It significantly improves the wear resistance, mechanical properties and thermal stability of composite materials, extends service life, and is suitable for high wear, high temperature and high speed working environments.
Smart Images

Figure BDA0005057768940000071 
Figure BDA0005057768940000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a high-wear-resistant ceramic-reinforced polymer composite material and a preparation method thereof. Background Art
[0002] Pure polymers are prone to adhesive wear in high-intensity wear environments due to their low surface hardness and poor load-bearing capacity, which limits their lifespan. In addition, organic polymer materials tend to soften or melt in high-temperature environments, and are prone to thermal decomposition and oxidative degradation, resulting in loss of performance.
[0003] The introduction of ceramic fillers can significantly improve these properties. Ceramics have excellent properties such as high modulus, high compressive strength, high temperature tolerance, high hardness and wear resistance, making them very attractive in extreme high temperature environments.
[0004] Therefore, it is necessary to develop a high wear-resistant ceramic-reinforced polymer composite. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide a highly wear-resistant ceramic-reinforced polymer composite material and a preparation method thereof. The composite material adopts polypropylene resin as a matrix, and is added with specially modified alumina ceramic fillers and carbon fiber reinforcement phases. By optimizing the formula ratio and injection molding process parameters, a composite material with excellent wear resistance, high strength and stable friction performance is prepared.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution: a highly wear-resistant ceramic-reinforced polymer composite material, in parts by weight, comprising:
[0007] Polypropylene resin: 55-75 parts;
[0008] Surface modified alumina ceramic filler: 15-35 parts;
[0009] Carbon fiber: 6-10 parts;
[0010] Silicon dioxide: 1-3 parts;
[0011] Other additives: 1-5 parts.
[0012] Optionally, the preparation method of the surface modified alumina ceramic filler is: placing alumina and γ-aminopropyltriethoxysilane in a reaction container, and reacting at 85-90° C. for 2.5-3 hours.
[0013] Optionally, the mass ratio of the γ-aminopropyltriethoxysilane to alumina is (3-5):100.
[0014] Optionally, the carbon fiber is electrochemically anodized.
[0015] Optionally, the electrochemical anodizing treatment conditions are: immersing the carbon fiber in a 10% sulfuric acid solution, with a voltage of 12-15V and a time of 25-30 minutes.
[0016] Optionally, the other auxiliary agents are heat stabilizers and antioxidants.
[0017] The present invention also provides a method for preparing a highly wear-resistant ceramic-reinforced polymer composite material, comprising the following steps:
[0018] Step (1): feed the raw materials into a twin-screw extruder according to the formula ratio of claim 1, with a melting temperature of 215-225° C. and a screw speed of 75-85 rpm, and melt mixing for 9-11 minutes. The extruded melt is water-cooled and pelletized to form composite material particles.
[0019] Step (2): Put the composite material particles of step (1) into an injection molding device, with a melting temperature of 225-235° C., an injection pressure of 105-115 MPa, a holding time of 11-13 seconds, and a cooling time of 22-27 seconds to obtain an injection molded product.
[0020] Step (3): subjecting the product after injection molding in step (2) to ion bombardment surface treatment, with ion energy of 85-95 keV and time of 1.5-2.5 min.
[0021] The present invention also provides the use of the above-mentioned high wear-resistant ceramic reinforced polymer composite material or the high wear-resistant ceramic reinforced polymer composite material prepared by the preparation method of the high wear-resistant ceramic reinforced polymer composite material in a texturizing machine or a false twisting machine.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The special surface modified alumina ceramic filler is used to achieve strong chemical bonding with the polymer matrix, greatly improving the wear resistance of the composite material; the unique carbon fiber surface treatment technology is used to form a strong interface bond between the carbon fiber and the polymer matrix, greatly improving the mechanical properties of the composite material; by optimizing the injection molding process parameters, such as melting temperature, injection molding pressure, etc., the surface quality and performance of the composite material are ensured to be stable, avoiding the defects of traditional processes; the ion bombardment treatment process is used to further improve the wear resistance and friction coefficient of the composite material to meet the requirements of high-speed working environment.
[0024] 2. Excellent wear resistance: By introducing ceramic fillers and carbon fiber reinforcement, the wear resistance of the composite material is 47% higher than that of traditional PP materials. This can effectively solve the problem of easy wear of the false twister of the texturing machine and greatly extend its service life.
[0025] 3. High strength and stable friction performance: This highly wear-resistant ceramic-reinforced polymer composite material uses a special surface modification technology to form a strong chemical bond between the ceramic filler and the polymer matrix, with a tensile strength of 85MPa. At the same time, the surface ion bombardment treatment increases the friction coefficient to 0.39, with good friction stability. This ensures that the false twister of the texturing machine can maintain reliable operation under high-speed operation conditions.
[0026] 4. Excellent thermal stability: The polypropylene resin matrix has good thermal stability. With the reinforcement of ceramic fillers, the composite material can be used stably for a long time in a high temperature environment above 200°C, meeting the requirements of high temperature working conditions of the texturing machine.
[0027] 5. Excellent processing performance: This highly wear-resistant ceramic-reinforced polymer composite material is prepared by injection molding technology, which can realize the integrated molding of complex components and greatly simplify the processing process; at the same time, the optimized injection molding parameters ensure the dimensional accuracy and surface quality of the product, further improving production efficiency.
[0028] 6. This highly wear-resistant ceramic-reinforced polymer composite material is suitable for the high-wear, high-temperature, and high-speed working environment of the false twister of the texturing machine. Compared with traditional materials, it can greatly improve the service life and working reliability of the false twister, thereby improving the production efficiency and economic benefits of the entire texturing machine. Therefore, this innovative composite material has broad application prospects in the field of false twisters of texturing machines. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1
[0031] The highly wear-resistant ceramic-reinforced polymer composite material in the embodiment of the present invention includes the following components in parts by weight: polypropylene resin (PP): 65 parts; surface-modified alumina ceramic filler: 25 parts; carbon fiber (CF): 8 parts; silicon dioxide: 2 parts; other additives: 3 parts, including 1.5 parts of thermal stabilizer and 1.5 parts of antioxidant.
[0032] The present application example provides a method for preparing a highly wear-resistant ceramic-reinforced polymer composite material:
[0033] (1) The raw materials were put into a twin-screw extruder according to the above formula ratio, with a melting temperature of 220° C. and a screw speed of 80 rpm. The melt was mixed for 10 min. The extruded melt was water-cooled and pelletized to prepare composite material particles.
[0034] (2) The composite material particles of step (1) are put into an injection molding device with a melting temperature of 220° C., an injection pressure of 110 MPa, a holding time of 12 seconds, and a cooling time of 25 seconds to obtain an injection molded product.
[0035] (3) The product after injection molding in step (2) is subjected to ion bombardment surface treatment, with an ion energy of 90 keV and a time of 2 min.
[0036] Example 2
[0037] The highly wear-resistant ceramic-reinforced polymer composite material in the embodiment of the present invention includes the following components in parts by weight: polypropylene resin: 55 parts; surface-modified alumina ceramic filler: 15 parts; carbon fiber: 6 parts; silicon dioxide: 1 part; other additives: 1 part, including 0.5 parts of heat stabilizer and 0.5 parts of antioxidant.
[0038] The present application example provides a method for preparing a highly wear-resistant ceramic-reinforced polymer composite material:
[0039] (1) The raw materials were put into a twin-screw extruder according to the above formula ratio, with a melt temperature of 215° C. and a screw speed of 75 rpm. The melt was mixed for 9 minutes. The extruded melt was water-cooled and pelletized to prepare composite material particles.
[0040] (2) The composite material particles of step (1) are put into an injection molding device with a melting temperature of 215° C., an injection pressure of 105 MPa, a holding time of 11 seconds, and a cooling time of 22 seconds to obtain an injection molded product.
[0041] (3) The product after injection molding in step (2) is subjected to ion bombardment surface treatment, with an ion energy of 85 keV and a time of 1.5 min.
[0042] Example 3
[0043] The highly wear-resistant ceramic-reinforced polymer composite material in the embodiment of the present invention includes the following components in parts by weight: polypropylene resin: 75 parts; surface-modified alumina ceramic filler: 35 parts; carbon fiber: 10 parts; silicon dioxide: 3 parts; other additives: 5 parts, including 2.5 parts of heat stabilizer and 2.5 parts of antioxidant.
[0044] The present application example provides a method for preparing a highly wear-resistant ceramic-reinforced polymer composite material:
[0045] (1) The raw materials were put into a twin-screw extruder according to the above formula ratio, with a melt temperature of 225° C. and a screw speed of 85 rpm. The melt was mixed for 11 minutes. The extruded melt was water-cooled and pelletized to prepare composite material particles.
[0046] (2) The composite material particles of step (1) are put into an injection molding device with a melting temperature of 220° C., an injection pressure of 115 MPa, a holding time of 13 seconds, and a cooling time of 27 seconds to obtain an injection molded product.
[0047] (3) The product after injection molding in step (2) is subjected to ion bombardment surface treatment, with an ion energy of 95 keV and a time of 2.5 min.
[0048] Comparative Example 1
[0049] The same as Example 1, except that unmodified alumina is used.
[0050] Comparative Example 2
[0051] Same as Example 1, except that the alumina is modified with amino.
[0052] Comparative Example 3
[0053] The same as Example 1, except that the surface modified alumina ceramic filler and carbon fiber are not added.
[0054] Comparative Example 4
[0055] The same as Example 1, except that no carbon fiber is added, wherein the added content of the surface modified alumina ceramic filler is 10%, 20%, and 30% respectively.
[0056] Comparative Example 5
[0057] The same as Example 1, except that the surface modified alumina ceramic filler is not added, wherein the carbon fiber addition content is 5%, 10%, and 15% respectively.
[0058] Comparative Example 6
[0059] The same as Example 1, except that the product after injection molding is subjected to plasma treatment.
[0060] Comparative Example 7
[0061] The same as Example 1, except that the injection molded product was not treated.
[0062] Examples 1-3 and Comparative Examples 1-2 were subjected to a tensile peel test to test the interfacial peel strength of each composite material. The test was based on GB / T 7124 standard (the results are shown in Table 1); Example 1 and Comparative Examples 3-5 were subjected to a wear resistance test using a ring-block wear tester according to GB / T 1040.1 standard. The test conditions were: load 500N, rotation speed 500r / min, and wear time 1000r (the results are shown in Table 2); Example 1 and Comparative Examples 6-7 were subjected to a dynamic friction coefficient test using a ring-block friction tester according to GB / T 3960 standard. The test conditions were: load 300N, sliding speed 1m / s, and friction time 30min (the results are shown in Table 3).
[0063] Table 1 Interface peeling strength of composite materials of Examples 1-3 and Comparative Examples 1-2
[0064]
[0065] It can be seen from Table 1 that silane coupling agent modification can significantly improve the interfacial bonding strength between alumina and polypropylene resin matrix, which is better than amino modification. This is because silane coupling agent can form chemical bonds on the ceramic surface, while amino modification mainly relies on physical adsorption and has weaker bonding strength.
[0066] Table 2 Effect of different filler types and contents on the wear resistance of composite materials
[0067]
[0068] It can be seen from Table 2 that with the increase of the content of alumina and carbon fiber, the wear resistance of the composite material continues to improve. This is because the ceramic filler and carbon fiber can effectively hinder the cutting and peeling of the abrasive particles, thereby improving the wear resistance of the composite material. Among them, the wear resistance volume loss of the composite material of Example 1 is 37%.
[0069] Table 3 Comparison of the effects of different surface treatment processes on the friction coefficient of composite materials
[0070] parameter Example 1 Comparative Example 6 Comparative Example 7 Dynamic friction coefficient 0.39 0.36 0.32
[0071] It can be seen from Table 3 that the ion bombardment surface treatment process can significantly improve the dynamic friction coefficient of the composite material, which is 21.9% higher than that of the untreated one. This is because ion bombardment forms a dense wear-resistant layer on the surface of the composite material, increases the surface roughness and chemical activity, and thus improves the friction performance with the mating part, while plasma treatment only increases the friction coefficient by 12.5% compared with the untreated one, and the effect is relatively limited.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly wear-resistant ceramic-reinforced polymer composite material, characterized in that: In parts by weight, it includes: Polypropylene resin: 55-75 parts; Surface modified alumina ceramic filler: 15-35 parts; Carbon fiber: 6-10 parts; Silicon dioxide: 1-3 parts; Other additives: 1-5 parts.
2. The highly wear-resistant ceramic-reinforced polymer composite material according to claim 1, characterized in that: The preparation method of the surface modified alumina ceramic filler is as follows: alumina and gamma-aminopropyltriethoxysilane are placed in a reaction container and reacted at 85-90° C. for 2.5-3 hours.
3. The highly wear-resistant ceramic-reinforced polymer composite material according to claim 2, characterized in that: The mass ratio of the γ-aminopropyltriethoxysilane to alumina is (3-5):
100.
4. The highly wear-resistant ceramic-reinforced polymer composite material according to claim 1, characterized in that: The carbon fiber is electrochemically anodized.
5. The highly wear-resistant ceramic-reinforced polymer composite material according to claim 4, characterized in that: The electrochemical anodizing treatment conditions are: immersing the carbon fiber in a 10% sulfuric acid solution, with a voltage of 12-15V and a time of 25-30 minutes.
6. The highly wear-resistant ceramic-reinforced polymer composite material according to claim 1, characterized in that: The other auxiliary agents are heat stabilizers and antioxidants.
7. The method for preparing a highly wear-resistant ceramic-reinforced polymer composite material according to any one of claims 1 to 6, characterized in that: The steps include: Step (1): feeding the raw materials into a twin-screw extruder according to the formula ratio of claim 1, with a melting temperature of 215-225° C. and a screw speed of 75-85 rpm, and melt mixing for 9-11 minutes. The extruded melt is water-cooled and pelletized to form composite material particles; Step (2): putting the composite material particles of step (1) into an injection molding device, with a melting temperature of 225-235° C., an injection pressure of 105-115 MPa, a holding time of 11-13 seconds, and a cooling time of 22-27 seconds to obtain an injection molded product; Step (3): subjecting the product after injection molding in step (2) to ion bombardment surface treatment, with ion energy of 85-95 keV and time of 1.5-2.5 min.
8. The high wear-resistant ceramic reinforced polymer composite material according to any one of claims 1 to 6 or the high wear-resistant ceramic reinforced polymer composite material prepared by the preparation method of the high wear-resistant ceramic reinforced polymer composite material according to claim 7, characterized in that: The highly wear-resistant ceramic-reinforced polymer composite material can be used in a texturing machine or a false twister.
Citation Information
Cited By
Ceramic nano composite yarn guide material as well as preparation method and application thereof
CN119192724A